A questionnaire survey exploring healthcare professionals' attitudes towards teamwork and safety in acute care areas in South Korea. Issue 7 (24th July 2015) - Kim, Sung Eun; Kim, Chan Woong; Lee, Sang Jin; Oh, Je Hyeok; Lee, Dong Hoon; Lim, Tae Ho; Choi, Hyuk Joong; Chung, Hyun Soo; Ryu, Ji Yeong; Jang, Hye Young; Choi, Yoon Hee; Kim, Su Jin; et al.
Abstract : Objectives: Although human factors are important in terms of patient safety, there have been very few reports on the attitudes of healthcare professionals working in acute care settings in South Korea. In the present study, we investigated the attitudes of such professionals, their cultures and their management systems. Design: A questionnaire survey with 65 items covering nine themes affecting patient safety. Nine themes were compared via a three-or-more-way analysis of variance, with interaction, followed by multiple comparisons among several groups. Setting: Intensive care units, emergency departments and surgical units of nine urban hospitals. Participants: 592 nurses and 160 physicians. Intervention: None. Outcome measures: Mean scores using a five-point scale and combined response scores for each of the nine themes. Results: The mean score for information-sharing was the highest (3.78±0.49) and that for confidence/assertion was the lowest (2.97±0.34). The mean scores for teamwork, error management, work value, organisational climate, leadership, stress and fatigue level, and error/procedural compliance were intermediate. Physicians showed lower scores in leadership and higher scores in information-sharing than nurses. Respondents with 24 months or less of a clinical career showed higher scores in leadership, stress and fatigue, and error scores and lower scores in work value than more experienced respondents. Conclusions: Our results suggest that medical personnel in Korea are relatively reluctant to disclose error or assert their different opinions with others. Many did not adequately recognise the negative effects of fatigue and stress, attributed errors to personal incompetence, and error-management systems were inadequate. Discrepancies in leadership and information-sharing were evident between professional groups, and leadership, stress, fatigue level, work value and error scores varied with the length of work experience. These can be used as baseline data to establish training programmes for patient safety in Korea.